Efektivitas Filial Play dalam Meningkatkan Kemampuan Orang Tua Meregulasi Emosi dan Empati selama Mendampingi Anak Belajar dari Rumah di Sekolah Maitreyawira, Deli Serdang - Halim, Shiesta Melisa; Milfayetty, Sri; Masganti, Masganti (Mahesa Research Center, 2022)
The purpose of this study was to describe the effectiveness of Filial Play in increasing the ability of parents to regulate emotions and empathize while accompanying children to learn from home at Maitreyawira school, Deli Serdang. Qualitative research method with a narrative research approach using NVIVO-12. The results showed that by being given Filial Play treatment, namely structuring skills, setting boundaries, attentive listening, and child-centered games for 3 months so that the informants could carry out Filial Play in a flexible and integrated manner. By applying the four Filial Play skills, parents become better able to regulate emotions by means of cognitive reappraisal and expression suppression. In addition, parents are better able to empathize, namely by understanding the child's point of view (perspective taking), placing oneself in the position of others (online stimulation), emotional contagion (emotional contagion), drifting/getting carried away with feelings (peripheral responsiveness), and sympathy/feel what is felt by the child (proximal responsiveness). There is an effectiveness of Filial Play in increasing the ability of parents to regulate emotions and empathize while accompanying children to learn from home.